Supramolecular assemblies constructed from inverted cucurbit[7]uril and lanthanide cations: synthesis, structure and sorption properties. Issue 81 (16th August 2016) - Li, Qing; Qiu, Sheng-Chao; Zhang, Yun-Qian; Xue, Sai-Feng; Tao, Zhu; Prior, Timothy J.; Redshaw, Carl; Zhu, Qian-Jiang; Xiao, Xin
Abstract : The interaction of a series of lanthanide cations (Ln 3+ ) with inverted cucurbit[7]uril (iQ[7]) in the presence of [ZnCl4 ] 2− anions as a structure-directing agent have been investigated. Abstract : The interaction of a series of lanthanide cations (Ln 3+ ) with inverted cucurbit[7]uril (iQ[7]) in the presence of [ZnCl4 ] 2− anions as a structure-directing agent have been investigated. Single-crystal X-ray diffraction analysis has revealed that the [ZnCl4 ] 2− anions surround the iQ[7] molecules via the outer surface interactions of iQ[7]. This results in the formation of honeycomb-like frameworks, and ultimately linear supramolecular chains of iQ[7] in which Ln 3+ cations occupy voids within the framework. Moreover, these iQ[7]/Ln 3+ -based supramolecular assemblies exhibit excellent thermal stability as well as permanent porosity, and in one case screening revealed a high CH3 OH uptake capacity compared with other porous organic materials assembled solely through hydrogen bonding under ambient conditions.